Religion and Conflict Attribution An Empirical Study of the Religious Meaning System of Christian, Muslim and Hindu Students in Tamil Nadu, India - Anthony, Francis-Vincent (Radboud Studies in Humanities, 2014)
Religion in a pluralistic society can play a dual role with regard to conflict. It can promote either violence or peace. Religion and Conflict Attribution examines the causes of interreligious conflict as perceived by Christian, Muslim and Hindu college students in Tamil Nadu, India. Readership: Academic institutions, researchers, post-graduate students and religious authorities interested in the scientific study of religion. The findings are of specific relevance to educationalists dealing with interreligious and intercultural issues.